2020
DOI: 10.1001/jamanetworkopen.2020.12469
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Reverse Fragility Index to Statistically Nonsignificant Randomized Clinical Trial Results

Abstract: IMPORTANCE Interpreting randomized clinical trials (RCTs) and their clinical relevance is challenging when P values are either marginally above or below the P = .05 threshold. OBJECTIVE To use the concept of reverse fragility index (RFI) to provide a measure of confidence in the neutrality of RCT results when assessed from the clinical perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 33 publications
1
64
0
Order By: Relevance
“…Similar studies examining the FI/RFI in broad research areas are common in the literature. 26 The protocol of the study was published at the Center for Open Science https:// osf. io/ mnx2c/.…”
Section: Research Question and Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Similar studies examining the FI/RFI in broad research areas are common in the literature. 26 The protocol of the study was published at the Center for Open Science https:// osf. io/ mnx2c/.…”
Section: Research Question and Search Strategymentioning
confidence: 99%
“…At the moment, there is no recognised cut-off for categorising either the FI or the RFI. 26 For the current analyses, 2×2 tables were created in Microsoft Excel and the Fischer's exact test was used to calculate and verify the FIs and RFIs of the included trials. For one trial, 31 32 the reported sample and events in each group were used to calculate the FI, and for another, 33 the incidence and the total number of participants allocated in each group were applied in the FI calculations.…”
Section: Calculation Of the Fi And Rfimentioning
confidence: 99%
See 1 more Smart Citation
“…RFI was calculated according to the method described in a recent publication. 8 The RFI was calculated by subtracting events from the group with a lower number of events while simultaneously adding nonevents to the same group to keep the number of participants constant until the Fisher's exact test two-sided p value became less than 0.05. 8 A similar method was used to calculate RFI at a p value of 0.01.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…To check the robustness of a statistically nonsignificant trial, reverse fragility index (RFI) has been used. 8 RFI provides a measure of robustness in the neutrality of results when assessed from a clinical perspective.…”
Section: Introductionmentioning
confidence: 99%